(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Unsatisfactory results of traditional methods of treatment of patients with uveal melanoma conditioned the search for a new complex approach to the organ-preserving therapy. Lately it has been shown that realization of the organ-preserving treatment depends on the activation of the immunologic systems of the patient’s organism. Purpose of the investigation. To study the possibility of using Amixin in the complex treatment of patients with uveal melanoma. Materials and methods. The investigation was carried out in 83patients with uveal melanoma. The patients were divided into two groups: I group — 43 patients with uveal melanoma who were made photocoagulation and ?-therapy against the background of interferon inductor — amixin; II group — 40 patients without using immunologic correction. There was also made the study of the level of expression of the molecular markers of lymphocyte activation CD7+ CD38+ CD45+, CD54+, CD95+, CD150+ by the histoimmunochemical method before the beginning of treatment, in 3 and 9 months after treatment. Results. The patients with uveal melanoma whose combined therapy was given against the background of amixin had the tumour prominence reliably higher than patients that did not take amixin and made 7.4 (SD 3.1) mm versus 5.8 (SD 2.9) mm, p+0.001 The tumour volume was also higher in patients that took amixin and made 66.8 (SD 32.7) mm3 and in patients who did not take amixin it was 52.8 (SD 31.2) mm3, p+0.05. Despite the fact that the tumour size in the group of patients taking amixin was higher, failures of the organ-reserving treatment was 7.4 % versus 23.8 % in the group of patients who did not have immunocorrection therapy. There was noted reliable increase of the level of CD95+ and CD7+ expression in 3 months after intake of amixin. In 9 months the patients who took amixin were ob-served to have reliable increase inn comparison with the initial level of expression of CD95+ CD25+ CD38+, CD54+ (only absolute indices), CD150+, CD45+, CD7+ In 3 months the level of molecular markers of lymphocyte activation did not increase reliably in patients with uveal melanoma whose combined therapy did not include amixin. In 9 months in comparison with the initial level there was noted reliable increase of the expression of relative content of CD95+, absolute content of CD150+, absolute and relative content of CD45+ and CD7+. Conclusion. It is established that inclusion of amixin in the complex therapy of patients with uveal melanoma allows to destruct tumours of the large size as well as contribute to reduction in the enucleation rate. The positive effect of using amixin in patients with uveal melanoma is associated with authentic increase of the expression level of CD54+ and CD95+ molecules promoting a positive result of the organ-preserving treatment.